Responding to the COVID-19 pandemic: Development of a critical care nursing surge model to meet patient needs and maximise competencies. Issue 1 (January 2022) - Lauck, Sandra B.; Bains, Vininder K.; Nordby, Dione; Iacoe, Emma; Forman, Jacqueline; Polderman, Jopie; Farina, Lena
Abstract: Background: The current coronavirus disease 2019 (COVID-19) pandemic is creating unprecedented and unchartered demands on critical care units to meet patient needs and adapt the delivery of health services. Critical care nurses play a pivotal role in developing models of care that are effective, flexible, and safe. Objectives: We report on the accelerated development of a critical care nursing surge model responsive to escalating needs for intensive care capacity. Methods: We conducted an exploratory prospective observational cohort study that included (i) a self-assessment and survey of learning needs of noncritical care nurses identified as candidate groups for redeployment in the intensive care unit and (ii) a pilot implementation of a team nursing model evaluated by individual questionnaires and the conduct of focus groups. We used descriptive statistics and qualitative content analysis to analyse the exploratory findings. Results: We surveyed 147 noncritical care nurses; 99 (67.3%) self-assessed at the lowest level of critical care competency, whereas 33 (24.3%) reported feeling able to help care for a critically ill patient under the direction of a critical care nurse. Identified learning needs included appropriate use of personal protective equipment in the intensive care unit (n = 123, 83.7%), use of specialised equipment (n = 103, 85.1%), basic mechanical ventilation, and vasoactive medication. We completed 11 team nursing pilot assignments with dyads of critical care and noncritical care nurses categorised in tiers of competencies. Nurses reported high levels of perceived support and provision of safe care; multiple recommendations were identified to improve the model of care delivery and communication. Conclusions: The complexity, acuity, and unpredictability of the COVID-19 pandemic is placing new demands on critical care nurses to modify existing processes for care delivery while ensuring excellent outcomes and professional satisfaction. The study findings provide a road map to support nursing engagement in meeting patient needs.